Darwinism and the Survival of Religion - Brooke, John Hedley (The Historical Review/La Revue Historique, 2019)
It is a great honour and privilege to give the Constantinos Th. Dimaras Lecture for 2016. I am grateful to the National Hellenic Research Foundation for the opportunity to do so and to Dr Efthymios Nicolaidis for kindly issuing the invitation. In our age of the internet, there are few topics that excite such strong opinions in the blogosphere as the relations between science and religion. Deeply embedded in the consciousness, both scholarly and popular, of Western Europe is the belief that science and religion have continuously been, and must be, in conflict. This belief has been described as “the idea that wouldn’t die”, despite excellent historical research drawing attention to its shortcomings.2 It is certainly not the only view. Those, including scientists themselves, who represent different religious traditions, have often argued that, when “science” and “religion” are properly understood, there can be a deeper relationship of harmony, or at least compatibility, between them. When, during the 1960s, I studied the history of science at Cambridge University, I realised that these two master narratives of conflict and harmony are too general to capture the complexity of historical controversy and debate.3 One of my aims in this lecture is to illustrate this complexity by examining religious responses to Charles Darwin’s theory of evolution.